Reflejo De La PsicologÃa Revolucionaria En El Comportamiento Del Individuo En Las Obras Literarias De Mariano Azuela E Isaac BÃ¡bel - Sadovska, Julia (European Scientific Journal, ESJ, 2018)
This paper focuses on the analysis of the psychology and the model of human behavior reflected in the works of M. Azuela and I. Babel. The novels "The ones of down" (M. Azuela) and "Red Cavalry" (I. Babel), dedicated to the revolution and the civil war, are explored within the framework of the social psychology. Theories of human behavior in the revolution, the aspect of motivation, and the socio-psychological mechanisms of its massive impact on the individual are considered. Similarly, the state of emotional stress that forces the masses to move was investigated. In the process of the "emotional whirlpool" and the "circular reaction" in progress, the voltage increases, which inevitably result to an explosion at the end (most of the time - of a violent nature). The parallel analysis of the researched works reveals that human behavior is determined by belonging to the consciousness of the masses or to the individual conscience. Individual consciousness and mass exist in a certain unity, but mass psychology, conquers the individual. In this case, a person becomes the "bearer of the mask" of the revolution.